A Working Class in the Making: Belgian Colonial Labor Policy, Private Entreprise, and the African Mineworker, 1907-1951 - Jewsiewicki, Bogumil (Labour / Le Travail, 1991)
The article reviews the book, "A Working Class in the Making: Belgian Colonial Labor Policy, Private Entreprise, and the African Mineworker, 1907-1951," by John Higginson.
Keywords: BOOKS – Reviews; LEHRER; Susan; Labor policy; Nonfiction; ORIGINS of Protective Labor Legislation for Women; 1905-1925 (Book)